2022
DOI: 10.3390/ijms23179700
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Gelatin Films Cross-Linked with Dialdehyde Cellulose Nanocrystals as Potential Materials for Wound Dressings

Abstract: In this study, thin chitosan-gelatin biofilms cross-linked with dialdehyde cellulose nanocrystals for dressing materials were received. Two types of dialdehyde cellulose nanocrystals from fiber (DNCL) and microcrystalline cellulose (DAMC) were obtained by periodate oxidation. An ATR-FTIR analysis confirmed the selective oxidation of cellulose nanocrystals with the creation of a carbonyl group at 1724 cm−1. A higher degree of cross-linking was obtained in chitosan-gelatin biofilms with DNCL than with DAMC. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 120 publications
1
9
0
Order By: Relevance
“…A general trend was observed, showing that an increase in the ratio of SOPP from 0% to 50% (w/w) within the gelatin film matrix led to a significant increase in the apparent density from 1.08 ± 0.02 in CFG (100/0) to 1.5 ± 0.08 in the G‐SOPP (50/50). These results were found to be similar, as already presented in the literature for gelatin‐based films incorporated with polysaccharide hydrocolloids 78,79 . This variation in apparent density can be attributed to the changes in solid content density and porosity of films by adding SOPP 80 .…”
Section: Resultssupporting
confidence: 88%
“…A general trend was observed, showing that an increase in the ratio of SOPP from 0% to 50% (w/w) within the gelatin film matrix led to a significant increase in the apparent density from 1.08 ± 0.02 in CFG (100/0) to 1.5 ± 0.08 in the G‐SOPP (50/50). These results were found to be similar, as already presented in the literature for gelatin‐based films incorporated with polysaccharide hydrocolloids 78,79 . This variation in apparent density can be attributed to the changes in solid content density and porosity of films by adding SOPP 80 .…”
Section: Resultssupporting
confidence: 88%
“…The suspension (film + supernatant) was then mixed with 5 mL of 0.06 mmol/L DPPH stock solution and allowed to react in the dark at ambient temperature for 30 min. The absorbance of the supernatant was measured at 517 nm and RSA% was calculated as described for PC (Wegrzynowska‐Drzymalska et al., 2022). All determinations were performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Cellulose nanocrystals are excellent biomaterials with tunable surface chemistry. Recently, several studies have been focused on the topic of modification of cellulose nanocrystals, such as by esterification, oxidation [ 43 ], carbamation, amidation, etherification [ 44 ]. In the past years, it has been reported that cellulose nanocrystals can be oxidized with periodate and form several aldehyde groups [ 45 ].…”
Section: Hydrogels As Biomaterialsmentioning
confidence: 99%
“…Therefore, dialdehyde cellulose nanocrystals may react with the free amino groups from chitosan or gelatin same as glutaraldehyde. This type of reaction is widely known as the Schiff base reaction [ 44 ].…”
Section: Hydrogels As Biomaterialsmentioning
confidence: 99%